A Primer for Spatial Econometrics With Applications in R - Arbia, Giuseppe. (Palgrave Texts in Econometrics, 2014)
This book aims at meeting the growing demand in the field by introducing the basic spatial econometrics methodologies to a wide variety of researchers. It provides a practical guide that illustrates the potential of spatial econometric modelling, discusses problems and solutions and interprets empirical results.